A Newly Discovered Genetic Disorder Associated With Life-Threatening Aortic Disease in a 6-Year-Old Boy. (February 2020) - Hamandi, Mohanad; Bolin, Madison L.; Fan, Joy; Lanfear, Allison T.; Woolbert, Seth K.; Baxter, Ronald D.; DiMaio, J. Michael; Brinkman, William T.
Aortic aneurysms in children are rare and when present are usually caused by a connective tissue disorder. In this article, we present a case of multiple aortic aneurysms in an adolescent with a novel finding of a gene variation that is associated with aortic disease.